FEATURES OF APPLICATION OF ECO-ORIENTED PEDAGOGICAL TECHNOLOGIES IN THE PROFESSIONAL TRAINING OF FUTURE SKILLED WORKERS IN MODERN MILITARY REALITIES (Innovative professional education, 2023)
The relevance of eco-oriented pedagogical technologies is substantiated, their features are analyzed, and the structural components of teachers’ readiness for development and application of these technologies in the professional training of future skilled workers are determined. The state of this issue is briefly highlighted in study of the readiness of teachers of VET schools to use eco-oriented pedagogical technologies in their work under martial law.
Keywords: vocational education, eco-oriented pedagogical technologies, design, readiness, professional training, methodology